2008
DOI: 10.1111/j.1348-0421.2008.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clostridium butyricum preparation concomitantly with Helicobacter pylori eradication therapy in relation to changes in the intestinal microbiota

Abstract: Antibiotic associated diarrhea due to human intestinal microbiota abnormalities is a side effect of H. pylori eradication therapy. We examined intestinal microbiota changes during H. pylori eradication therapy and the preventive effect of CBM588 as a probiotic agent. Nineteen patients with gastro-duodenal ulcer were randomly divided into three groups: group A (without probiotics), group B (with regular doses of CBM588) and group C (with double doses of CBM588). The incidence of diarrhea and soft stools during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 31 publications
(33 reference statements)
1
48
0
2
Order By: Relevance
“…To clarify the duration of this effect, Buhling et al [90] showed that the eradication therapy exerted only a short-term influence on gut flora, whereas another study observed long-term disturbances even 9 weeks after treatment was complete. Probiotics, defined as microorganisms with potentially beneficial health effects, such as Lactobacilli, is assumed to prevent or at least partly diminish the microbial disturbances [89,92]. Probiotics, defined as microorganisms with potentially beneficial health effects, such as Lactobacilli, is assumed to prevent or at least partly diminish the microbial disturbances [89,92].…”
Section: H Pylori Eradication and The Alterations Of Microbiotamentioning
confidence: 99%
“…To clarify the duration of this effect, Buhling et al [90] showed that the eradication therapy exerted only a short-term influence on gut flora, whereas another study observed long-term disturbances even 9 weeks after treatment was complete. Probiotics, defined as microorganisms with potentially beneficial health effects, such as Lactobacilli, is assumed to prevent or at least partly diminish the microbial disturbances [89,92]. Probiotics, defined as microorganisms with potentially beneficial health effects, such as Lactobacilli, is assumed to prevent or at least partly diminish the microbial disturbances [89,92].…”
Section: H Pylori Eradication and The Alterations Of Microbiotamentioning
confidence: 99%
“…All patients with influenza virus H7N9 infection showed a sharp increase in inflammatory markers in the blood, caused by the primary and secondary infections. There are many reports of anti-inflammatory activity of probiotics, including CBM588 [10,33]. With regard to the assessment of microecological treatment strategies, treatment of H7N9 infection has previously focused on pathogenicity because of the translocation and virulence of probiotics [34], and conflict between antibiotics that kill bacteria and microecological regulatory agents that promote bacterial growth, so that the negative effects did not outweigh the benefits.…”
Section: Discussionmentioning
confidence: 99%
“…CBM588 ( Clostridium butyricum 588 strain MIYA-BM tablets; Miyarisan Pharmaceutical, Tokyo, Japan) prevents antibiotic-associated diarrhea [10] and has anti-inflammatory effects in the colon as a result of butyric acid production [11]. We retrospectively assessed the effects of microbiota restoration strategies on restoring intestinal homeostasis under antibiotic exposure, and on reducing the risk of secondary infection, by real-time monitoring of the shift in predominant intestinal bacteria using quantitative polymerase chain reaction (qPCR) and PCR-based denaturing gradient gel electrophoresis (PCR-DGGE).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evaluated whether probiotic supplementation might help to prevent or reduce drug‐related side effects during H. pylori eradication therapy in adults [61,63,64,66,68,69,72–75,78–80]. All showed that diarrhea, nausea and taste disturbances were significantly reduced by probiotics and overall they were superior to placebo for side effect prevention.…”
Section: Clinical Studiesmentioning
confidence: 99%